Traum - Mantik - Allegorie Die Hieroi Logoi des Aelius Aristides im weiteren Kontext der griechisch-römischen Traumliteratur - Bittrich, Ursula (Millennium-Studien / Millennium Studies, 2017)
The highly metaphorical language that is used in the dream narratives of the Hieroi Logoi written by the Mysian orator Aelius Aristides has hitherto hardly been assessed in a manner adequate to its depth. In her interpretation of this text that turns out to be heavily loaded with religious meaning, the author of the present monograph deploys an allegorical approach that emerges from her analyses of relevant oneirocritical texts and literature.